Timeliness of diagnosis in Motor Neurone Disease: a population-based study - Donaghy, Colette (The Ulster Medical Society, 2008)
Following the observation from our experience with the Northern Ireland Motor Neurone Disease (MND) register that excessive delays appeared to exist in the diagnosis of patients with MND, we performed a population-based study of the length and factors involved in the diagnostic process. In 73 patients we found that the median time to diagnosis from symptom onset was 15.6 months, being shorter in bulbar onset patients and longer in females or those presenting with non-specific gait disturbance. We divided this interval into three time periods – symptom onset to first medical contact, first medical contact to neurology referral and neurology referral to diagnosis. The time period from first medical contact to neurology referral was the longest of the three periods studied indicating that appropriate timely referral of patients to neurologists was responsible for the greatest delay in making a diagnosis of MND. We propose that improving the accessibility of neurological services could potentially reduce the time to diagnosis by at least three months.